Does a closer coach-athlete bond buffer or exacerbate the detrimental effects of controlling coaching on athletes` coping and outcomes? - Lefever, E.; Flamant, N.; Morbée, S.; Soenens, B.; Vansteenkiste, M.; Ntoumanis, N.; Bartholomew, K.; De Cocker, K.; Haerens, L. (International Journal of Sports Science and Coaching, 2024)
Some coaches are convinced that controlling practices will not harm their athletes if they simultaneously are warm and caring. This study, grounded in Self-Determination Theory and Skinner's coping framework, explored these convictions among 179 volleyball players (67.6% female; age = 21.12 ± 4.66 years). Participants assessed perceived controlling and relatedness-supportive coaching styles, their coping strategies, self-reported performance, engagement, competitive anxiety, and burnout. Results showed that controlling coaching related to reduced performance, and more competitive anxiety and burnout. Controlling coaching associated indirectly with these athletes` outcomes through compulsive compliance. Finally, when coaches were perceived to display moderate or high levels of relatedness-support, controlling coaching related to worse performance, and more competitive anxiety. These results suggest that a closer coach-athlete bond may exacerbate the detrimental impact of controlling coaching, as athletes feel internally pressured to obey the coach's demands without internally accepting these commands.